The ecology of the mangroves of South Florida a community profile. - Odum, William E. (Washington, D.C. US Fish & Wildlife Service, Office of the Biological Service, 1982)
Biological Services Program; FWS/OBS-81/24
Keywords: Mangrove swamps; Mangrove ecology